Search for new phenomena in final states with large jet multiplicities and missing transverse momentum with ATLAS using √s = 13 TeV proton-proton collisions - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physics letters, 2016)
Results are reported of a search for new phenomena, such as supersymmetric particle production, that could be observed in high-energy proton-proton collisions. Events with large numbers of jets, together with missing transverse momentum from unobserved particles, are selected. The data analysed were recorded by the ATLAS experiment during 2015 using the 13 TeV centre-of-mass proton-proton collisions at the Large Hadron Collider, and correspond to an integrated luminosity of 3.2 fb−1. The search selected events with various jet multiplicities from ≥7 to ≥10 jets, and with various b-jet multiplicity requirements to enhance sensitivity. No excess above Standard Model expectations is observed. The results are interpreted within two supersymmetry models, where gluino masses up to 1400 GeV are excluded at 95% confidence level, significantly extending previous limits.